MANAJEMEN PROGRAM SISTER SCHOOL DALAM MENINGKATKAN MUTU INTERNASIONALISASI SEKOLAH DI SMA LABSCHOOL UNESA 1 SURABAYA - Masyqi Salma; Supriyanto Supriyanto (STKIP Pesisir Selatan, 2026)
The sister school program is an educational internationalization strategy aimed at enhancing school quality through collaboration with overseas educational institutions. This study aims to describe the management of the sister school program in improving the quality of school internationalization at SMA Labschool UNESA 1 Surabaya. The study employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, document analysis, and a literature review, and subsequently analyzed using the interactive model developed by Miles, Huberman, and Saldana, which encompasses data condensation, data display, and conclusion drawing. The results indicate that the management of the sister school program has systematically and sustainably implemented management functions, including planning, organizing, implementation, and evaluation. The program's implementation has positively impacted the quality of school internationalization by developing students' global competencies, improving English communication skills, strengthening an internationally oriented school culture, and expanding collaborative networks with overseas educational institutions. This study demonstrates that the success of school internationalization is determined not only by the existence of international partnerships but also by the quality of program management capable of sustainably integrating international dimensions into the learning process and school governance.